The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jsr.13669
|View full text |Cite
|
Sign up to set email alerts
|

Frontal white matter association with sleep quality and the role of stress

Abstract: An important measure of brain health is the integrity of white matter connectivity structures that link brain regions. Studies have found an association between poorer sleep quality and decreased white matter integrity. Stress is among the strongest predictors of sleep quality. This study aimed to evaluate the association between sleep quality and white matter and to test if the relationship persisted after accounting for stress. White matter microstructures were measured by diffusion tensor imaging in a popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In the study by Manzanares et al (2021), besides finding high stress levels, high resilience levels were observed despite COVID-19. Kuo et al (2020) Bruce et al, 2022;David et al, 2022;Jowkar et al, 2022;Karimi et al, 2022;Kim et al, 2022). Another study that compared stress and sleep disorders during the first wave of COVID-19 and 9 months later found that this association was not only cross-sectional but also longitudinal (Ballesio et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Manzanares et al (2021), besides finding high stress levels, high resilience levels were observed despite COVID-19. Kuo et al (2020) Bruce et al, 2022;David et al, 2022;Jowkar et al, 2022;Karimi et al, 2022;Kim et al, 2022). Another study that compared stress and sleep disorders during the first wave of COVID-19 and 9 months later found that this association was not only cross-sectional but also longitudinal (Ballesio et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Stress partially mediated the relationship between FS and SQ. Previous studies have demonstrated the association between having higher levels of stress and poorer SQ among college students [47,48]. FS is demonstrated by the fact that children can communicate with their parents about the difficulties they encounter and receive some emotional support and material resources to solve their problems through their families, thus eliminating the burden of stress and further improving their SQ problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one prior study investigated how the interaction between sleep and stress affected the white matter tracts of elderly subjects [ 3 ], and found that poor sleep quality induced more changes than did stress; no mediation effect of sleep and stress was apparent. However, even if sleep disturbances exert stronger effects than stress, the effects of such disturbances associated with stress should differ from those of sleep disturbances without stress.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes have been reported in the internal capsule, corona radiata, thalamus, and frontal regions of insomnia patients. [3][4][5] Thus, white matter neural connectivity may be compromised by sleep problems.Life stress could also affect white matter. Patients with depression who were exposed to high levels of life stress exhibited greater increases in white matter hyperintensity volumes than did those exposed to less stress, despite similar levels of depression.…”
mentioning
confidence: 99%
See 1 more Smart Citation